Artificial tethering to nuclear pores promotes partitioning of extrachromosomal DNA during yeast asymmetric cell division - Khmelinskii, Anton; Meurer, Matthias; Knop, Michael; Schiebel, Elmar (Current biology, 2011)
SUMMARY: Asymmetric cell division in unicellular organisms enables sequestration of senescence factors to specific subpopulations. Accumulation of autonomously replicating sequence (ARS) plasmids, which frequently emerge from recombination within the highly repetitive ribosomal DNA locus, is linked to limited replicative life span of Saccharomyces cerevisiae cells [1]. During budding yeast cell division, ARS plasmids are retained in the ageing mother cell, such that only 1 out of 10 plasmids enters the rejuvenated bud [2]. Binding of ARS plasmids to nuclear structures retained in the mother cell was speculated to explain asymmetric plasmid segregation [2]. Association with nuclear pore complexes (NPCs) was proposed to underlie retention of ARS plasmids in the mother cell [3]. However, the role of NPCs in segregation of ARS plasmids is unclear, as NPCs are partitioned between mother and bud nuclei during mitosis [4,5]. Here we analyzed how segregation of ARS plasmids is influenced by their interaction with NPCs. We found that artificial tethering to NPCs promotes transport of ARS plasmids into the bud. Moreover, our experiments provide support for the notion that interaction with ARS plasmids does not affect movement of NPCs into the bud. We conclude that binding to NPCs cannot by itself contribute to asymmetric segregation of ARS plasmids.
Gesehen am 11.08.2017